Vertically aligned ultrathin MoSe2 nanoflakes grown on carbon cloth and its field emission behaviour. (August 2019) - Dusane, Pravin R.; Thombare, Balu R.; Bankar, Prashant K.; Lole, Gaurav; Gavhane, Dnyaneshwar; Khedkar, Chaitali V.; Nagrare, Bhagyashree; Salunkhe, Ashwini; Kolhe, Pankaj; Choudhary, Ram J.; Phase, D.M.; More, Mahendra A.; et al.
Graphical abstract: Highlights: In-situ synthesis of ultrathin MoSe2 nanoflakes on carbon cloth (MS-C) under hydrothermal route. Use of carbon cloth facilitates fabrication of flexible field emitters for practical applications. Superior field emission properties were observed for MS-C as compared to MoSe2 powder (MS-P) emitter. Maximum current density (5.372 mA/cm 2 ) was obtained at 500 μm separation. The present synthesis protocol can be extended to synthesize high aspect ratio nanostructures of other TMDs. Abstract: In this paper, MoSe2 nanoflakes on carbon cloth (MS-C) and MoSe2 powder (MS-P) were synthesized by facile hydrothermal route. The synthesized MoSe2 nanoflakes, owing to their high aspect ratio, are envisaged as potential candidates for field emitters. Accordingly, field emission (FE) characteristics of MoSe2 nanoflakes were investigated at the base pressure of 1 × 10 -8 mbar. The FE properties were studied at three different anode-cathode separations (500, 1000 and 1500 μm). The observed values of turn-on and threshold fields are comparable to those exhibited by nanostructures and nano-composites of other TMDs. Moreover, the MS-C emitter showed competency to deliver very high emission current density of 5.372 mA/cm 2 at an applied electric field of 8 V/μm. The MS-C emitter exhibited good emission stability at pre-set value of 100 μA and hardly any degradation in emission current was noticed over duration of 10 h. The use of carbon cloth as a substrate is two-fold advantageous, a substrate having very good electrical conductivity and mechanical flexibility. The observed results imply that the present synthesis protocol (carbon cloth as substrate and hydrothermal route) can be efficiently employed to fabricate flexible field emitters for practical applications in vacuum micro/nanoelectronic devices.